Rwanda : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines the Joint Staff Assessment of Rwanda's Poverty Reduction Strategy Paper (PRSP) progress report. The authorities have showed continued commitment to privatization of public enterprises. Financial management reform is on track, as are established targets in the social sectors, particularly for education. Rwanda's PRSP targets annual real GDP growth rates in the range of 7-8 percent a year in the near future, supported by improved agricultural productivity and an expansion in nonagricultural demand for goods and services.